Development Of Education In Post Tsunami Aceh - Mujiburrahman, Mujiburrahman (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2012)
Discussing about the development of education in Aceh is not far from the aspect of Aceh’s long history. The development of education in Aceh has run in some phases. Education is very broad but this paper focuses only on aspects of education development in Aceh post-tsunami. Discussions on the development of education in post-tsunami Aceh focus on two aspects, namely formal and informal education. Earthquake and tsunami hit Aceh on December 26, 2004 had extremely changed many aspects of life, including education aspects. The data from the Department of Education reports that 25,000 students and 2,248 teachers died and 2153 school buildings were destroyed or heavily damaged. As a result, Aceh education sectors were in severe condition. It is not exaggerated to say that education in Aceh was coming into